مدى ممارسة أساليب المحاسبة الإبداعية في المنشآت الحكومية السورية ( دراسة ميدانية ) - الشيخ, سهيل (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى اختبار مدى وجود هذه الظاهرة في المنشآت الحكومية السورية، وفي حال وجودها ما هي الإجراءات المحاسبية المستخدمة في ذلك؟ وقد توصل البحث إلى عدم وجود الظاهرة بالنسبة لمجمل الإجراءات الواردة في النظام، ما عدا بعض الإجراءات مثل: عدم مراجعة العمر الإنتاجي للأصل الثابت في الربع الأخير من عمره الإنتاجي المقدر، وتضمين مخزون آخر المدة بالمخزون الراكد أو المتقادم، وإخفاء الديون المتعثرة لهدف تخفيض الديون المشكوك فيها، وتاخير إثبات فواتير مشتريات قرابة نهاية العام لإثباتها في العام التالي للتأثير على نتائج أعمال العام وإجراءات أخرى. The aim of this research is to test the phenomenon existence at the Syrian government installations, and if does exist , what are the accounting procedures used in it?. The research Finding provide evidence that this phenomenon does not exist regarding Total procedures in this System, except some procedures Such as ,not reviewed the productive life of fixed assets at the fourth quarter of its estimated productive life , and merge the last term stock with idle stock, and Disappearance of bad Debts , in order to Reduce doubtful Debts, and delaying proof of purchase invoices at the end of the years to provide it in the following year in order to have an effect on the years business .